How to MEK the best of uveal melanoma: A systematic review on the efficacy and safety of MEK inhibitors in metastatic or unresectable uveal melanoma. (November 2018) - Steeb, Theresa; Wessely, Anja; Ruzicka, Thomas; Heppt, Markus V.; Berking, Carola
Abstract: Background: BRAF and MEK inhibitors have demonstrated significant survival benefits for patients with cutaneous melanoma. However, their use for uveal melanoma (UM) is less established. The aim of this systematic review was to summarise the current evidence on the efficacy and safety of MEK inhibitors in metastatic UM. Methods: We performed a systematic literature search in MEDLINE, Embase and the Cochrane Library CENTRAL from 1946 through 17 April 2018. Abstracts of oncologic conferences, trial registers and reference lists were handsearched for relevant publications. The risk of bias was assessed with the Cochrane Risk of Bias Tool. Results: Of 590 records identified, six studies met the eligibility criteria and were included in the qualitative synthesis. Data were available for selumetinib ± dacarbazine (n = 3), trametinib ± AKT inhibitor (n = 2) and binimetinib plus sotrastaurin (n = 1) from three open-label phase II, two open-label phase I and one placebo-controlled phase III trial. The overall response rate was available in five studies and ranged from 0 to 14% with an average of 2.5%. The median progression-free survival ranged from 3.1 weeks to 16 weeks. Data on overall survival and 1-year survival rates were not consistently reported. Severe treatment-related adverse events were observed most commonly for the combination use of selumetinib plus dacarbazine (62%) and binimetinib plus sotrastaurin (75%). Conclusion: UM is little responsive to MEK inhibition, regardless of the inhibiting agent and combination partner. Our results do not support the use of MEK inhibitors in UM. Novel treatment options are urgently needed in this patient population. Highlights: Metastatic uveal melanoma (UM) is an orphan disease of a high unmet need. The current use of MEK inhibitors in UM is not evidence based. A systematic review on the use of MEK inhibitors for UM was performed. MEK inhibitors have low radiologic response rates in UM.